Italy and EU enlargement to the Western Balkans: the Europeanization of national interests?. Issue 4 (2nd October 2017) - Frontini, Andrea; Denti, Davide
Abstract: Italy is a vocal supporter of EU enlargement to the Western Balkans. Relying on primary and secondary sources and semi-structured interviews, this article analyses Italy's position, including the 'what?' (the traditional views of the country on EU enlargement), the 'how?' (formal processes and actual practices of decision-making) and the 'why?' (the main factors influencing its position). The expected economic and security benefits for Rome largely compensate for the perceived costs of EU enlargement towards the region. Nevertheless, Italy's influence capacity is hampered by lack of resources and a traditional focus on mere diplomatic presence, as it emerges from the recent examples of the Berlin Process, the refugee crisis, and the EUSAIR.